2008
DOI: 10.1001/archsurg.143.9.901
|View full text |Cite
|
Sign up to set email alerts
|

Planned Early Discharge–Elective Surgical Readmission Pathway for Patients With Gallstone Pancreatitis

Abstract: Hypothesis: We assessed outcomes in patients with gallstone pancreatitis (GSP) managed using a readmission pathway of discharge from the index admission with early readmission cholecystectomy and compared these with conventional management. We hypothesized that the pathway would decrease hospital length of stay (LOS).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…This may reflect the lack of available operating time on routine lists together with poor prioritisation. On the other hand, this and other observational studies 18,24 have shown that the LOS during the index admission increases if patients undergo definitive treatment during that admission. It may be necessary to book patients with mild GSP for a cholecystectomy once the diagnosis has been made, even if they are still settling, as this has been shown to be safe and reduce LOS 25,26 .…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…This may reflect the lack of available operating time on routine lists together with poor prioritisation. On the other hand, this and other observational studies 18,24 have shown that the LOS during the index admission increases if patients undergo definitive treatment during that admission. It may be necessary to book patients with mild GSP for a cholecystectomy once the diagnosis has been made, even if they are still settling, as this has been shown to be safe and reduce LOS 25,26 .…”
Section: Discussionmentioning
confidence: 52%
“…One study found that 31% of recurrent GSP occurred in the first two weeks following discharge 17 . In another study when patients were discharged home but operated on within two weeks this figure was 6.5% 18 . This further study also suggested that performing definitive treatment during the index admission increases the length of hospital stay (LOS).…”
mentioning
confidence: 95%
“…one of these studies, done in 2003, showed a 20% rate of recurrence in those patients who were managed with cholecystectomy more than 2 weeks after onset of pancreatitis (8). Although most prospective data is poorly powered, and sparse, there are a handful of small prospective studies that have also confirmed that for mild disease, early cholecystectomy is beneficial compared to delaying surgery beyond 2 weeks (10,11). one study even showed that the reduction in recurrences made early cholecystectomy cost effective (12).…”
Section: Mild Pancreatitsmentioning
confidence: 99%
“…1,2 It is a bundle of "best evidence-based practices" delivered by a multi-professional health care team, with the intention of assisting patients to recuperate expeditiously after surgery. 1 Clinical, or critical, pathways have been described to improve outcomes in various fields of surgery, [3][4][5][6][7][8][9][10][11][12][13][14][15][16] including colorectal surgery. [17][18][19][20][21][22][23] Clinical pathways designed for the colorectal surgery patient have resulted in decreased hospital length of stay (LOS); decreased cost; and decreased, or no difference, in morbidity rates when compared to conventional care.…”
Section: Introductionmentioning
confidence: 99%